Pengaruh Current Ratio (CR) dan Return On Equity (ROE) Terhadap Devident Payout Ratio (DPR) Pada Perusahaan Perkebunan Yang Terdaftar Di Bursa Efek Indonesia (BEI) Sebelum dan Sesudah Pandemi Periode 2018 -2022 - Muhammad Alfarizi; Romli, Harsi; Munandar, Aris (Universitas Indo Global Mandiri, 2024)
This research aims to investigate the influence of Current Ratio (CR) and Return On Equity (ROE) on Dividend Payout Ratio (DPR) both simultaneously and partially. The study was conducted on Plantation Companies listed on the Indonesia Stock Exchange (IDX). The data used in this study is quantitative, sourced from secondary data obtained from www.idx.co.id. The population determined by the author for this study is plantation companies listed on the Indonesia Stock Exchange Before and After the Pandemic period from 2018 to 2022. Sampling was done using purposive sampling, resulting in 6 companies selected as research samples, thus totaling 30 observations from 6 companies x 5 years observation period. Data analysis in this study was conducted using Eviews 12 software program. The research results indicate that there is a simultaneous influence of Current Ratio (CR) and Return On Equity (ROE) on Dividend Payout Ratio (DPR) with a Prob (F-statistic) value of 0.001553, which is smaller than 0.05. Partially, there is an influence of Current Ratio (CR) on Dividend Payout Ratio (DPR) with a probability value of 0.0093, which is smaller than 0.05, and there is an influence of Return On Equity (ROE) on Dividend Payout Ratio (DPR) with a probability value of 0.0077, which is smaller than 0.05. The coefficient of determination test (R2 test) reveals an R-squared value of 0.814048 or 81.40%, while the remaining 18.9% is explained or described by other variables not included in this study Keywords: Current Ratio (CR), Return On Equity (ROE), Devident Payout Ratio (DPR)